CultureFun: An Interactive Web-Based Cultural Learning Platform Using a Human-Computer Interaction Approach - Syaqilla Maulidia; Najjuan Al Fariz; Andhika Presha Saputra; Muhammad Darwis (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study aimed to develop CultureFun, a user-centered web-based platform for cultural learning among younger generations. The study addressed the limitation of existing digital cultural learning media, which often rely on text-heavy content and provide limited interactivity. User-Centered Design and Design-Based Research were applied to guide needfinding, empathy-based analysis, iterative prototyping, and usability evaluation. Data were collected through semi-structured interviews and direct observation involving twelve participants aged 10–23 years. The final prototype was evaluated using the System Usability Scale. The results showed that CultureFun was perceived as easy to use and engaging, particularly because the platform presented short cultural content supported by images, quizzes, and mini-games. The platform achieved an average usability score of 72.08, indicating good and acceptable usability. This study concludes that integrating user-centered analysis, iterative prototyping, and gamified interaction can support the development of an effective and usable digital cultural learning platform. However, the findings were limited by the small sample size and the focus on usability rather than direct measurement of learning effectiveness. Future studies are recommended to involve more diverse participants and examine long-term cultural knowledge retention.